Behind the thinking of attention disorder - Zamboni, Daniela; Snyder, Vicki (Frontiers in Psychology, 2025)
This article presents an innovative exploration of attention disorders by focusing on their cognitive structure and the power of neuroplasticity, moving beyond traditional models that primarily emphasize lessening behavioral manifestations. By employing Reuven Feuerstein’s theory of Structural Cognitive Modifiability, it examines the cognitive architecture of individuals with attention disorders, emphasizing the dynamic interplay between cognitive processes, neuroplasticity, and behavioral outcomes. The paper identifies distinct cognitive patterns influencing focus, organization, and planning, which manifest in diverse presentations of inattention. It highlights the potential for precise, individualized cognitive interventions to address inefficiencies in information processing, foster self-regulation, and enhance brain adaptability. By addressing the origins rather than the complaints this approach offers a transformative framework for enhancing self-regulation, cognitive adaptability, and overall learning outcomes in individuals with attention disorders.